2016
DOI: 10.3390/ijms17122056
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective Effect of Cuscuta campestris Yunck. Whole Plant on Carbon Tetrachloride Induced Chronic Liver Injury in Mice

Abstract: Cuscuta seeds and whole plant have been used to nourish the liver and kidney. This study was aimed to investigate the hepatoprotective activity of the ethanol extract of Cuscuta campestris Yunck. whole plant (CCEtOH). The hepatoprotective effect of CCEtOH (20, 100 and 500 mg/kg) was evaluated on carbon tetrachloride (CCl4)-induced chronic liver injury. Serum alanine aminotransferase, aspartate aminotransferase, triglyceride and cholesterol were measured and the fibrosis was histologically examined. CCEtOH exhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 30 publications
1
13
0
1
Order By: Relevance
“…Regarding the protection study, the observed physical and behavioral response of mice to CCl 4 has also been described previously [26]. The hepatic and renal damage of CCl 4 are well documented and the histopathological findings present are comparable to the literature data [3][4][5]. Accordingly, hepatic centrilobular area and the renal proximal tubules are major xenobiotic transformation sites and particularly sensitive to chemical insults, since they contain biotransformation enzymes from the cytochrome P450 family, which mediate the formation of toxic metabolites and reactive intermediates [27,28].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Regarding the protection study, the observed physical and behavioral response of mice to CCl 4 has also been described previously [26]. The hepatic and renal damage of CCl 4 are well documented and the histopathological findings present are comparable to the literature data [3][4][5]. Accordingly, hepatic centrilobular area and the renal proximal tubules are major xenobiotic transformation sites and particularly sensitive to chemical insults, since they contain biotransformation enzymes from the cytochrome P450 family, which mediate the formation of toxic metabolites and reactive intermediates [27,28].…”
Section: Discussionsupporting
confidence: 81%
“…Conventional drugs have limited efficacy and availability, as well as side effects associated with prolonged use [2], highlighting the need for alternative treatments. Many plant extracts and plant-derived compounds are often tested using animal models for their potential in hepato-and nephroprotective activities against hepatotoxic agents such as the well characterized carbon tetrachloride (CCl 4 ) [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Although different parameters were obtained from different studies, the underlying mechanisms mainly focus on reducing oxidative stress, decreasing inflammatory response, suppressing apoptosis, and blocking lipid peroxidation, resulting in normalizing serum and hepatic biomarkers and in improved histopathological conditions. Herbs like Polygonum multiflorum , Rosa laevigata Michx, Rourea induta Planch., and Cuscuta campestris Yunck have shown hepatoprotective effects in rodent models, even though the extracts were isolated from different parts of the plants or with different extracting solutions (Kalegari et al., ; Lee, Huang, Duh, & Wu, ; Peng et al., ; Zhang et al., ). Formulas of traditional medicines have been used based on the thought that some ingredients could work synergistically and avoid side effects.…”
Section: Protective Effects Of Natural Products On Pollutant‐induced mentioning
confidence: 99%
“…Modern pharmacological studies have revealed that CS can act in various parts of the body, including the reproductive [ 21 , 22 ] and immune [ 23 , 24 , 25 ] systems, and exerts biological functions such as anti-oxidant [ 26 , 27 , 28 ] and anti-cancer [ 29 , 30 ] effects. In addition, some reports have suggested that CS can prevent and treat liver [ 28 , 31 , 32 , 33 , 34 ] and neurodegenerative-related [ 35 ] diseases.…”
Section: Introductionmentioning
confidence: 99%